THE EFFECT TO USING PhET SIMULATION AS A SCIENCE LEARNING MEDIA ON JUNIOR HIGH SCHOOL STUDENTS’ CONCEPT MASTERING - Karisma Tiara Khoirunisa; Ellyna Hafizah; Mella Mutika Sari (Universitas Bhinneka PGRI, 2024)
Mastery of the concept is needed to measure the success of students' learning process. The objectives of this study were 1) To describe the mastery of the concept of dynamic electricity in class IX students at Junior High School Negeri 26 Banjarmasin who taught using PhET media, and 2) To describe whether or not there was an effect of using PhET as a learning medium in class IX at Junior High School Negeri 26 Banjarmasin. The type of research used is quantitative research with quasi-experimental methods and a nonequivalent control group research design. The data in this study is collected from the test (pre-test and post-test), which contain cognitive domains. The data analysis techniques used to test the hypothesis are the N-gain and simple linear regression tests. The result showed: 1) There were differences in the mastery of concepts in the control class and the experimental class as seen from the post-test average scores, namely 47,94 and 74,76; 2) There is an increase in students' mastery of concepts in the experimental class with an N-gain score in the experimental class of 54,09 in the medium category and the control class 22,76 in the low category; and 3) There is an effect of using PhET media on increasing mastery of students’ concepts by 52% based on the results of simple linear regression test. Using PhET media with the guided inquiry method positively influences and increases students' mastery of concepts.